Evaluation of Blended Learning Model of HighScope and Montessori at TK Early Step Kebagusan South Jakarta - Ajat, Ajat; Amaliani, Rita (Kirana Publisher (KNPub), 2025)
The title of the research is Evaluation of Blended Learning Model of HighScope and Montessori at TK Early Step Kebagusan Jakarta Selatan. The research aims to find out how the implementation and success of the Blended Learning Model of HighScope and Montessori in TK Early Step, as well as evaluate to get optimal results in a learning model program. This study uses a qualitative approach with the CIPP model which includes Context, Input, Process, and Product. The data sources in this study are the Vice Principal, Program and Curriculum Coordinator, Student Coordinator, Group A and Group B class teachers, students and parents of students. Data collection through inteviews, observations and documentation. Based on the results of the context findings, 80% of the documentation shows that the blended learning model has a legal basis and goals that are quite good in accordance with the vision, mission and school graduation standards. The results of the Input findings, interviews showed that the planning and program were good, educators and students were quite good in running the blended model, and the parents of students were quite good in supporting blended learning model. The results of the process findings, interviews show that the coordination of learning programs is quite good with the socialization of educators, students and parents of students, the implementation of learning is quite good, and learning supervision is quite good. The results of the product findings, questionnnaires from 90 students, a significant P value of P = 0.8 (80%) show that by applying the blended learning model, students develop their social-emotional well.